Western Balkans Regular Economic Report No.18, Fall 2020 : An Uncertain Recovery - World Bank (World Bank, Washington, DC, 2020)
As elsewhere in the world, in the Western Balkans the COVID-19 pandemic has plunged countries into deep recession. Because of the recession, labor market conditions have taken a turn for the worse and welfare improvements have been interrupted, although government response measures cushioned the blow. Policy efforts in the region need to remain focused on fighting the pandemic, limiting the economic damage and facilitating recovery.